TINDAKAN KOLEKTIF MASYARAKAT JARINGAN DI INDONESIA: AKTIVISME SOSIAL MEDIA PADA AKSI #GEJAYANMEMANGGIL - Hasna, Sofia (Master of Communication Science Program, Universitas Diponegoro, 2022)
The action that initiated by Aliansi Rakyat Bergerak on September 23, 2019 is one of the phenomena associated to responding the socio-political issues that become polemic in Indonesia that will be brought during the mass action in Gejayan Yogyakarta. This study uses a qualitative approach with a case study method that focuses on extracting various data like books and journal articles related to social media activism on #GejayanMemanggil. The research aims to find out the practice of #GejayanMemanggil social media activism. This research in the finding that in this action the emergence of collective action on the network society in Indonesia, namely this phenomenon is in accordance with the use of social media on 73,8 % of the society and students and society utilizing it through the hashtag #GejayanMemanggil which reached trending topic on Twitter in 23rd September 2019 with 4215 tweets. interPolitical participation to build collective awareness is built through the resource mobilization paradigm because of the mobilization system that is built both through offline and online activities through the use of social media.